Pemanfaatan Pelayanan Kesehatan Tradisional Integrasi di Rumah Sakit Pemerintah. Studi di 5 Provinsi Indonesia - Suharmiati Suharmiati; Lestari Handayani; Zainul Khaqiqi Nantabah (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2020)
Nowadays, Traditional Health Services increasingly in demand by the Indonesian Community. According to the National Basic Health Research data of 2018, 31.4% of the population utilized THS. Moreover, the practice of traditional medicine has widely provided in several places. Traditional health services at public hospitals are known as integrated traditional health services (ITHS). This study aims at analyzing the utilization of integrated traditional health services at public hospitals by the community in ﬁ ve provinces. This study, a descriptive with a cross-sectional design, involved ten public hospitals. It selected according to the availability of traditional health services, which is before or since 2014. The number of patients (called respondents) interviewed was determined purposively as many as ﬁ ve patients per hospital; therefore, there were ﬁ fty people. The results of this study indicated that Integrated Traditional Health Services has utilized by most patients aged 20 to 50 years. Information sources regarding the availability of Traditional Health Services mainly from physicians or health professionals. Most respondents lived not far from hospitals so that access to the hospitals can be reachable. Most respondents are satisﬁ ed with the services accepted. Manager of Traditional Health Services is a physician. Even though most respondents said that not only the cost of treatment for Traditional Health Services is expensive, but also is not covered in beneﬁ t packages of the National Health Insurance Scheme (JKN). Therefore, they remain seeking Traditional Health Services practicing out of pocket payment method. It is recommended that the ﬁnancing of Traditional Health Services should be covered by Social Security Administration Body (BPJSK) through